AI-powered recommendations: the roles of perceived similarity and psychological distance on persuasion. Issue 8 (30th December 2021) - Ahn, Jungyong; Kim, Jungwon; Sung, Yongjun
Abstract: Artificial intelligence (AI) plays various roles in our daily lives, such as personal assistant, salesperson, and virtual counselors; thus, it stands out in various fields as a recommendation agent. This study explored the effects of perceived similarity and psychological distance on the persuasion of AI recommendation agents through two experiments. Results of Experiment 1 elucidated that individuals feel more psychologically distant when they interact with AI recommendation agents than with human agents as a result of a different level of perceived similarity. Furthermore, psychological distance plays a mediating role in determining the effectiveness of desirability- vs. feasibility-focused messages in health-related issues. In Experiment 2, we manipulated the AI speaker's level of perceived similarity via anthropomorphism and found that the AI's recommendation with secondary (vs. primary) features is more effective when AI is humanized, and the reverse was found in non-humanized AI conditions. Both theoretical and managerial implications are provided.